Increasing Research Productivity: The Impact of Knowledge Management Applications in University Research Environments. (1st March 2015) - Hossain, Nargis; Bischoff, John; Willy, Christopher; Roncace, Robert; Walsh, Thom
Abstract : Scientists and universities strive to produce a large volume of high‐quality research. Universities supply the resources to enable scientific inquiry, such as the recently developed knowledge management (KM) tools. The use of KM platforms varies substantially in different environments. We examined the association between the use of KM tools and research productivity among four state universities in New York using analysis of variance techniques. We found a significant positive association. Important limitations are noted, and implications for both the study and the use of KM tools are discussed. Copyright © 2015 John Wiley & Sons, Ltd.